The physics behind semiconductor technology - Winnacker, Albrecht 1942- (Springer, 2022)
This textbook teaches the physics and technology of semiconductors, highlighting the strong interdependence between the engineering principles and underlying physical fundamentals. It focuses on conveying a basic understanding of the physics, materials, and processes involved in semiconductor technology without relying on detailed derivations. The book features separate comments on the key physical principles covered, allowing the reader to quickly grasp the take-home message. Chapter-end questions and answers round out this compact book, making it a helpful and dependable resource for physicists, electrical engineers, and materials scientists working with electronic materials. Aimed at upper-level undergraduate students and written by an author with extensive experience in both industry and academia, this textbook gives physicists the opportunity to learn about the materials and technology behind semiconductors, while providing engineers and materials scientists a deeper understanding of the physics behind the technology